Awareness Regarding Health Insurance Scheme in Selected Community of Banke District - Shah, Rekha (Academia Research Journal, 2025)
This study assessed awareness regarding health insurance schemes among residents of Banke District, Nepal. A descriptive cross-sectional design was employed, with data collected from 60 participants aged 40–59 years in Khajura Rural Municipality using non-probability purposive sampling. A semi-structured interview questionnaire was administered to evaluate awareness levels, with data analyzed using descriptive statistics in SPSS version 16. Findings revealed that 36.7% of respondents learned about health insurance through media (TV, radio, newspapers), while only 23.3% received information from insurance agents. Regarding perceptions, 36.7% associated health insurance with coverage for illness, injury, and death, while 16.7% linked it to post-death financial support. Most respondents (63.3%) believed health insurance provides free medical care, and 56.7% identified government hospitals as the primary service providers. Awareness levels were distributed as follows: 58.3% had average awareness, 26.7% demonstrated poor awareness, and only 15% exhibited good awareness. The study highlights significant gaps in understanding, particularly among older, less educated, and rural populations. These findings align with prior research in similar settings, underscoring the need for targeted community education programs to improve health insurance literacy. Despite limitations in generalizability due to the localized sample, the study contributes to the growing body of evidence on health insurance awareness in low-resource settings and suggests policy interventions should focus on improving outreach and simplifying communication about insurance benefits.